Routledge handbook of sport and social media - Billings, Andrew C.; Hardin, Marie C. (ROUTLEDGE, 2025)
This handbook takes an in-depth look at the transformative impact of social media on sport. With broader and deeper coverage than any previous book on this topic, the handbook explores how sports media is co-created and curated, collectively, at the individual, group and organisational level, and considers the implications for the ways in which sports media, through social media, infiltrates our lives and influences local and global culture. Exploring key concepts and presenting original case studies, the book features work by world-leading international sports media scholars. It discusses the theoretical lenses through which we can understand social media and sport, from political economy and cultural dynamics to business and management, and explains the significance of global social media platforms. The book then presents a multi-level exploration of sport and social media, including social media use by fans, athletes, teams, leagues and media organisations. Offering important new insight into a technology that now sits at the centre of our social and economic lives, this book is important reading for any researcher, student, practitioner or policymaker with an interest in sport media, sport business, sport cultures, digital media technologies, digital business, or the broader relationships between sport, media and wider society.